Pentingnya Kurikulum Darurat COVID-19 Bagi Pendidikan Indonesia - Iskandar, Sofyan; Rosmana, Primanita Sholihah; Fauziyyah, Dewi Hasna; Hasanah, Isma Aulia; Nada, Lulu Nadiatun; Puradireja, Shifa Mutiara (JURNAL SINEKTIK, 2023)
The curriculum is a design of all activities made by the school. The curriculum is not only about the subject matter and knowledge, but all the design of school activities. Therefore, this research aims to find out about the importance of the COVID-19 curriculum for Indonesian Education. This research uses a qualitative method of literature study. With the technique of collecting relevant and correct data, so that the research carried out is in accordance with the expected napa. The results obtained are all aspects that are directly related to the learning design that has been made, these learning activities and assessments are learning outcomes that are synchronized with the current emergency conditions that can be and felt directly by all educational units, therefore the learning process in this emergency curriculum must run, even though it is carried out online.